Abnormal findings in peers during skills learning. (3rd February 2016) - Wearn, Andy; Nakatsuji, Miriam; Bhoopatkar, Harsh
Summary: Background: Peer physical examination (PPE), where students examine each other, is common in contemporary clinical skills learning. A range of benefits and risks have been explored in the literature. One persistent concern has been the identification and management of abnormal physical findings. Two previous studies have attempted to quantify the risk, one through the discussion of two exemplar cases and the other with a retrospective student survey. Methods: Here, we report the first prospective study of the number and type of abnormalities encountered as part of early clinical skills learning in a medical programme. We have a formal written consent process for PPE, which includes the management of abnormal findings through the completion of an event form. Our data come from cohorts undertaking years 2 and 3 of the programme between 2003 and 2014. One persistent concern (of PPE) has been the identification and management of abnormal physical findings Results: Nineteen event forms were completed over this period. The incidence rates per year ranged from 0.23 to 1.05 per cent. Abnormal findings included raised blood pressure, heart murmur, abnormal bedside test values, and eye and skin conditions. Discussion: The low event rate, along with a feasible process for dealing with this issue, goes some way to reassuring those with concerns. We acknowledge that some abnormalities may have been missed, and that some data may have been lost as a result of incorrect process; however, even the highest annual rate is low in absolute terms. We recommend a formal process for managing abnormalities. Ideally this would be part of an overall PPE written policy, communicated to students, enacted by tutors and approved by the local ethics committee.